The Moderating Role Of Gender On The Influence Of Work Life Balance And Job Satisfaction On Employee Engagement (A Study Of Generation Z Employees In Malang City) - Siti Hotijah; Pardiman Pardiman; Muhammad Sirojuddin Amin (Aksaqila International Humanities and Social Sciences [AIHSS] Journal, 2026)
This study aims to examine the effects of work-life balance and job satisfaction on employee engagement among Generation Z employees in Malang City and to test the moderating role of gender in these relationships. A quantitative explanatory approach was employed using a survey method involving 400 respondents selected through purposive sampling. Data were collected using a Likert-scale questionnaire and analyzed using Partial Least Squares Structural Equation Modeling (PLS-SEM) with SmartPLS software. The results reveal that both work-life balance and job satisfaction have positive and significant effects on employee engagement. However, gender does not moderate the relationships between work-life balance, job satisfaction, and employee engagement. These findings suggest that employee engagement among Generation Z is primarily driven by work-life balance and job satisfaction rather than gender differences. The study implies that organizations should prioritize human resource policies that promote work-life balance and enhance job satisfaction to strengthen employee engagement, particularly among Generation Z employees in the contemporary work environment